Crafting an Entrepreneurship Strategic Planning Model for Islamic Boarding Schools Through a Comprehensive Literature Review - Saiful Irfan; Maria Veronika Roesminingsih; Mudjito Mudjito (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This study aims to describe entrepreneurship planning strategies in Islamic boarding schools through a literature review. Method: This qualitative descriptive study employs library research to investigate entrepreneurship strategic planning models for Islamic boarding schools. Initially, articles were gathered on the topic in the last decades, with subsequent refinement resulting in a selection of 20 relevant articles. Results: The literature review navigates through entrepreneurship education in Islamic boarding schools, bringing together various perspectives, approaches, and results. Common surface themes include the amalgamation of entrepreneurial endeavors with religious principles, the quest for financial self-sufficiency, and the diverse effects on students, institutions, and local communities. Novelty: The novelty in this literature review lies in synthesizing diverse perspectives on entrepreneurship education in Islamic boarding schools. The unique intersection of entrepreneurial activities with religious values and the pursuit of economic independence offers a distinctive lens for understanding the dynamics of entrepreneurship education in this context.